LEVERAGING ARTIFICIAL INTELLIGENCE IN EDUCATION: A COMPREHENSIVE ANALYSIS - Jurayev, Sherali Bozorboyevich (Innovative Development in Educational Activities, 2023)
This scientific article delves into the growing application of artificial intelligence (AI) in the field of education. As technology continues to advance, AI has emerged as a disruptive force, revolutionizing traditional teaching and learning methodologies. This article explores the various ways AI is being used in educational settings, its potential benefits and challenges, as well as its implications for the future of education.